Personality traits and emotional intelligence in internal drug dependent patients in two rehabilitation centers of Lima East - Raúl Stifp Zela Bravo (2019)
Objective: To determine the relationship between personality traits and emotional intelligence indrug-dependent patients, from 14 to 18 years old, inmates in two rehabilitation centers in Lima East.Methodology: The type of study is quantitative, correlational in scope and cross-sectional. The sampleconsisted of 153 participants. The model of the personality traits on which we work is the model ofthe big five of Costa and McCrae (1992). The scale to measure personality traits was the NEO FFIPersonality Inventory (abbreviated version), whose Peruvian adaptation was carried out by Martínezand Cassaretto (2005). To measure emotional intelligence levels, we used the Emotional IntelligenceInventory ICE BARON (abbreviated version), prepared by Baron (1997) and adapted by Ugarrizaand Pajares (2011). Results: It was evidenced that there is no significant relationship between bothstudy variables. In addition, no significant relationship was found between emotional intelligence withthe dimensions of extroversion, neuroticism, openness to experience, kindness and responsibility.Conclusion: there are other factors that intervene in the relationship of personality traits with theemotional intelligence of the participants.